2009
DOI: 10.1111/j.1468-3083.2009.03245.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate therapy at Gran Canaria on vitamin D production, blood glucose and lipids in patients with psoriasis

Abstract: Background Climate therapy (heliotherapy) of psoriasis is an effective and natural treatment. Ultraviolet radiation (UVB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 30 publications
8
35
2
2
Order By: Relevance
“…Serum levels of 25(OH)D increased during treatment with artificial UV (BUVB and NBUVB) and during heliotherapy (56)(57)(58)(59). The increase in 25(OH)D was higher in the BUVB treated patients when compared to the NBUVB (p=0.008) and heliotherapy (p=0.017) treated groups.…”
Section: The Effects Of Phototherapy On Vitamin D Status In Patients mentioning
confidence: 77%
See 3 more Smart Citations
“…Serum levels of 25(OH)D increased during treatment with artificial UV (BUVB and NBUVB) and during heliotherapy (56)(57)(58)(59). The increase in 25(OH)D was higher in the BUVB treated patients when compared to the NBUVB (p=0.008) and heliotherapy (p=0.017) treated groups.…”
Section: The Effects Of Phototherapy On Vitamin D Status In Patients mentioning
confidence: 77%
“…Low-dose NBUVB treatment significantly increased vitamin D status in patients with psoriasis, atopic eczema and other skin disorders with low initial levels of 25(OH)D (60,61). Within the following intervention studies, age showed no correlation with the observed increase in 25(OH)D levels (57,58,62). This indicates the skin's capacity to produce vitamin D3 during phototherapy of psoriasis is independent of the patient's age or psoriasis severity.…”
Section: The Effects Of Phototherapy On Vitamin D Status In Patients mentioning
confidence: 79%
See 2 more Smart Citations
“…Osmancevic et al (165) showed that psoriasis symptoms improved in twenty patients aged 25-65 years with 15 d of climate therapy in Gran Canaria. The LDL:HDL ratio decreased from 2·4 to 1·9 mmol/l (P, 0·001), apoA1 and HDL-cholesterol concentration increased and apoB decreased during the sun exposure period.…”
Section: Dyslipidaemiamentioning
confidence: 99%